The great American sports page a century of classic columns from Ring Lardner to Sally Jenkins - Pierce, Charles P. (Library of America, 2019)
"Spanning nearly a century, The Great American Sports Page presents essential columns from more than three dozen masters of the press-box craft. These unforgettable dispatches from World Series, Super Bowls, and title bouts for the ages were written on deadline with passion, spontaneity, humor, and a gift for the memorable phrase. Read avidly day in and day out by a sports-mad public, these columnists became journalistic celebrities in their home cities, their coverage trusted and savored, their opinions hotly debated. Some even helped change the games they wrote about. Gathered here in a groundbreaking anthology, their writings capture some of sport's most enduring moments and many of its all-time greats: Babe Ruth, Jackie Robinson, Muhammad Ali, and Michael Jordan among them. But the best American sportswriters also found ways to write powerfully about lesser-known athletes and to convey, often with heartbreaking honesty and insight, the less glamorous and more tragic facets of the games we love. In its survey of the finest American sportswriting from Ring Lardner to Thomas Boswell, from Red Smith and Jimmy Cannon to Bob Ryan and Michael Wilbon, The Great American Sports Page takes the measure of the human richness, complexity, and competitive spirit of sports and the athletes who continue to fascinate and inspire us."--Amazon.com
Keywords: Geschichte 1916-2014; Sportberichterstattung; Zeitung; Sportpublizistik; USA